Lesser Cornstalk Borer Damage to Sugarcane and the Effects of Tillage and Harvest Residue Management - Hardev S. Sandhu; Leslie E. Baucum; Gregg S. Nuessly (EDIS)
This 6-page fact sheet provides an overview of this pest, its damage to sugarcane, and the plant’s response, and describes the results of a study of harvest residue and controlled tillage experiments. Written by Hardev S. Sandhu, Leslie E. Baucum, and Gregg S. Nuessly, and published by the UF Department of Entomology and Nematology, May 2012.